Potential antioxidant and cytoprotective effects of essential oil extracted from Cymbopogon citratus on OxLDL and H2O2 LDL induced Human Peripheral Blood Mononuclear Cells (PBMC) - Jamuna S.; Sakeena Sadullah M.S.; Ashokkumar R.; Gokul Shanmuganathan; Senguttuvan Sivan Mozhi; Niranjali Devaraj S. (Food Science and Human Wellness)
Cymbopogon citratus (lemon grass) is commonly used in traditional folk medicine. The essential oil extracted from C. citratus has been reported as a potential anti-oxidant and anti-inflammatory agent. This study has been designed to explore the protective effect of C. citratus (lemon grass) against modified LDL (OxLDL and H2O2 LDL) induced cytotoxicity in Peripheral Blood Mononuclear Cells (PBMC). The essential oil extracted from C. citratus (EOC) was subjected to FT-IR spectroscopic analysis for the identification of functional groups. In vitro antioxidant assays were carried out to assess the electron donating capability of EOC as compared with a known standard L-ascorbic acid. The cytoprotective effects of EOC were determined in PBMC induced with modified LDL. Spectra obtained from FT-IR analysis showed the presence of functional groups in EOC such as H-bonded, OH stretching, NH stretching, aldehydeCH stretching, aldehyde/ketoneCO stretching, CC-stretching, CH3 bending, CH in plane bending. EOC has greater antioxidant property when compared with the standard L-ascorbic acid. EOC at all test concentrations demonstrated free radical scavenging activity and cytoprotective effect when challenged against modified LDL in PBMC. The above results show EOC as a promising antioxidant and cytoprotective agent.